Using zoobenthos and ichthyofauna as test objects for the quality of surface waters polluted with heavy metals - V. V. Butsiak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
In conditions of full-scale military operations, a global technogenic load is exerted on the environment, particularly water bodies and water supply sources. The assessment of the quality indicators of water bodies largely depends on the reliability and efficiency of control. Instrumental control methods do not allow for assessing the complex impact of xenobiotics present in water on the water body's ecosystem. Given this, it is necessary to use biological observation methods, which have become particularly relevant in recent decades. That is why we studied the impact of the increased content of mobile forms of heavy metals in surface waters on the reaction-response of zoobenthos and ichthyofauna as bioindication test objects. For this purpose, the following were investigated: the biotic index of the aquatic environment, the amount of phytoplankton, and the reaction response of hydrophones to the increased content of heavy metals in the marine environment. Organoleptic, physicochemical, and hydrochemical quality indicators of water were studied in the laboratory using classical methods. Chronic toxicity was studied in the selected water samples using bioindication methods (classical methods) and hydrophones as test objects. Studies of microbial water pollution (biotic index) of the Dobrotvir reservoir revealed rod-shaped, coccal forms and vibrios with a total biomass of bacterial populations at 9.6 μg/dm3. The most common representatives of algae in the water were green (44.8 %), blue-green (21.8 %), diatoms (20.6 %), and euglena (12.8 %). As a result of studies on the color change of chironomid larvae under the combined influence of heavy metals (Copper + Manganese + Zinc) for 96 hours, a comprehensive ecological assessment of this aquatic environment was established, which corresponded to the III (satisfactory) and IV (transitional) indices. By visual examination of the behavioral response of the ichthyofauna of the reservoir, we observed vivid manifestations of morphogenetic deviations; the value of the indicator of stability of the development of the frequency of asymmetric manifestation was established within 0.40–0.44, which corresponded to class 4 – significant deviations from the norm. In laboratory conditions, we studied the chronic combined effect of heavy metals (Cu + Mn + Zn) in doses of 1, 2, and 5 MPC on the dynamics of the vital activity of aquarium guppies with an exposure duration of 80 days. At the end of the exposure, 60 to 80 % of the studied fish in the experimental groups and 10 % in the control died. Thus, aquarium guppies can be used to qualitatively assess heavy metal pollution in the aquatic environment.